11
$\begingroup$

I'm sure you can do this easily, but I'm looking for an easy way that only uses series manipulation. Is that possible?

$$\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(\frac{1+n}{2}\right)-\psi^{(0)}\left(\frac{n}{2}\right)-\frac{1}{n}\right)$$

where $\psi^{(0)}(x)$ is digamma function

Here is a supplementary question, the alternating version

$$\sum_{n=1}^{\infty} (-1)^{n+1} \left(\psi^{(0)}\left(\frac{1+n}{2}\right)-\psi^{(0)}\left(\frac{n}{2}\right)-\frac{1}{n}\right)$$ And this one will take into account our year as a power $$\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(\frac{1+n}{2}\right)-\psi^{(0)}\left(\frac{n}{2}\right)-\frac{1}{n}\right)^{2014}$$

$\endgroup$
  • 2
    $\begingroup$ What's $\psi^{(0)}$ here? $\endgroup$ – Simon S Nov 4 '14 at 13:10
  • $\begingroup$ @SimonS I added the details. $\endgroup$ – user 1357113 Nov 4 '14 at 13:12
  • $\begingroup$ Were you investigating the asymptotics of $~2^{-N}\cdot\displaystyle\prod_{n=1}^N \frac{\Gamma\bigg(\dfrac{n+1}2\bigg)}{\Gamma\bigg(\dfrac n2+1\bigg)}$ ? $\endgroup$ – Lucian Nov 4 '14 at 19:18
  • 1
    $\begingroup$ @SimonS: $\displaystyle\psi^{(0)}(x)=\left(\frac{\mathrm{d}}{\mathrm{d}x}\right)^0\psi(x)=\psi(x)$. Don't ask me why; I'm just answering :-) $\endgroup$ – robjohn Nov 4 '14 at 20:52
4
$\begingroup$

You can calculate the series by combining the even and the odd summands. This yields:

$$\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(\frac{1+n}{2}\right)-\psi^{(0)}\left(\frac{n}{2}\right)-\frac{1}{n}\right)=\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(\frac{1+2n-1}{2}\right)-\psi^{(0)}\left(\frac{2n-1}{2}\right)-\frac{1}{2n-1}+\psi^{(0)}\left(\frac{1+2n}{2}\right)-\psi^{(0)}\left(\frac{2n}{2}\right)-\frac{1}{2n}\right)=\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(n\right)-\psi^{(0)}\left(n-\frac{1}{2}\right)-\frac{1}{2n-1}+\psi^{(0)}\left(n+\frac{1}{2}\right)-\psi^{(0)}\left(n\right)-\frac{1}{2n}\right)=\sum_{n=1}^{\infty} \left(\psi^{(0)}\left(n+\frac{1}{2}\right)-\psi^{(0)}\left(n-\frac{1}{2}\right)-\frac{1}{2n-1}-\frac{1}{2n}\right)=\sum_{n=1}^{\infty} \left(\frac{2}{2n-1}-\frac{1}{2n-1}-\frac{1}{2n}\right)=\sum_{n=1}^{\infty} \left(\frac{1}{2n-1}-\frac{1}{2n}\right)=\ln(2) $$ The last result follows form the series expansion of $\ln(1+x)$.

$\endgroup$
  • $\begingroup$ You're welcome! :) $\endgroup$ – Redundant Aunt Nov 4 '14 at 18:18
5
$\begingroup$

Main Question

We can telescope the first sum: $$ \begin{align} \lim_{N\to\infty}\sum_{n=1}^N\left[\psi\left(\frac{n+1}2\right)-\psi\left(\frac{n}2\right)-\frac1n\right] &=\lim_{N\to\infty}\left[\psi\left(\frac{N+1}2\right)-\psi\left(\frac12\right)-H_N\right] \end{align} $$ In this answer it is shown that $H_{-1/2}=-2\log(2)$; therefore, $\psi\left(\frac12\right)=-2\log(2)-\gamma$.

Asymptotically, $H_n=\gamma+\log(n)+O\left(\frac1n\right)$; therefore, $\psi(x)=\log(x)+O\left(\frac1x\right)$.

Thus, $$ \begin{align} &\lim_{N\to\infty}\left[\psi\left(\frac{N+1}2\right)-\psi\left(\frac12\right)-H_N\right]\\ &=\lim_{N\to\infty}\left[\log\left(\frac{N}2\right)+2\log(2)+\gamma-\log(N)-\gamma+O\left(\frac1n\right)\right]\\[4pt] &=\log(2) \end{align} $$


A Formula For Later Use

Starting with $$ \begin{align} \psi(x) &=-\gamma+\sum_{k=0}^\infty\left(\frac1{k+1}-\frac1{k+x}\right)\tag{1}\\ &=-\gamma+H_{x-1}\tag{2} \end{align} $$ we get $$ \begin{align} \psi\left(\frac{n+1}2\right)-\psi\left(\frac{n}2\right) &=\sum_{k=0}^\infty\left(\frac1{k+\frac{n}2}-\frac1{k+\frac{n+1}2}\right)\\ &=2\sum_{k=0}^\infty\left(\frac1{2k+n}-\frac1{2k+n+1}\right)\\ &=2\sum_{k=0}^\infty\frac1{(2k+n)(2k+n+1)}\tag{3} \end{align} $$ Using $n=1$ and $\psi(1)=-\gamma$ in $(3)$, we get $$ -\gamma-\psi\left(\frac12\right)=2\log(2)\tag{4} $$ which is an alternate proof that $\psi\left(\frac12\right)=-2\log(2)-\gamma$.


Supplementary Question

We can apply $(3)$ to $$ \begin{align} &\sum_{n=1}^{2N}(-1)^n\left[\psi\left(\frac{n+1}2\right)-\psi\left(\frac{n}2\right)-\frac1n\right]\\ &=-\log(2)-\gamma+2\sum_{n=1}^N\left[\psi\left(n+\frac12\right)-\psi(n)\right]-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+4\sum_{n=1}^N\sum_{k=0}^\infty\frac1{(2k+2n)(2k+2n+1)}-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+4\sum_{n=1}^N\sum_{k=n}^\infty\frac1{2k(2k+1)}-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+4\sum_{k=1}^\infty\sum_{n=1}^{\min(k,N)}\frac1{2k(2k+1)}-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+4\left[\sum_{k=1}^N\frac1{2(2k+1)}+\sum_{k=N+1}^\infty\frac{N}{2k(2k+1)}\right]-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+4\left[\frac12\left(H_{2N+1}-\frac12H_N-1\right)+\frac14+O\left(\frac1N\right)\right]-\psi\left(N+\frac12\right)\\ &=-\log(2)-\gamma+\left[2H_{2N+1}-H_N-1\vphantom{\frac1N}\right]-\log(N)+O\left(\frac1N\right)\\ &=-\log(2)-\gamma+\left[2(\gamma+\log(2)+\log(N))-(\gamma+\log(N))-1\vphantom{\frac1N}\right]-\log(N)+O\left(\frac1N\right)\\ &=\log(2)-1+O\left(\frac1N\right) \end{align} $$ Thus, changing the sign and taking the limit, we get $$ \sum_{n=1}^\infty(-1)^{n+1}\left[\psi\left(\frac{n+1}2\right)-\psi\left(\frac{n}2\right)-\frac1n\right] =1-\log(2) $$

$\endgroup$
  • $\begingroup$ Very good! (+1) $\endgroup$ – user 1357113 Nov 5 '14 at 8:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.